Дослідження тривалості обслуговування громадського транспорту на зупинних пунктах - Ройко, Юрій; Артимович, Павло; Плесак, Михайло (ТзОВ «Галицька видавнича спілка», 2021)
Components of public transport service duration at stopping points depending on its intensity are determined. It is established that such duration depends not only on passenger variability but on the duration of entering the stopping point and exiting it.
Investigation of public transport service duration at stopping points
Keywords: 656.051